Advances and Potentials of NiOx Surface Treatments for p−i−n Perovskite Solar Cells. Issue 3 (10th November 2021) - Tiwari, Nidhi; Arianita Dewi, Herlina; Erdenebileg, Enkhtur; Narayan Chauhan, Ram; Mathews, Nripan; Mhaisalkar, Subodh; Bruno, Annalisa
Abstract : The performances of perovskite solar cells (PSCs) largely depend on the perovskite compositions and the selection of electron and hole transport layers (ETLs and HTLs). The p‐type NiO x films are largely used as HTLs in p‐i‐n PSCs, thanks to their high transparency, processing versatility, cost‐effectiveness, and easy integration within tandem devices. Several studies have shown that surface modifications on NiO x films remove the surface defects, increase the NiO x conductivity, and alter the band offset, consequently improving the interfaces between NiO x films and the perovskite active layer. Indeed, besides improving the NiO x intrinsic properties, the surface treatments also lead, in many cases, to superior perovskite quality driving high photovoltaic performance. Abstract : Herein, surface modifications based on physical (UV−ozone, oxygen, argon, and/or helium plasma), chemical (interlayer passivation), and doping treatments and their impacts on the structural and optoelectronic properties of NiO x are discussed. The effects of modified NiO x films in p−i−n perovskite solar cells' (PSCs') power conversion efficiency (PCE) are also examined together with the current challenges and future outlooks.